Viability and Vigor of Thorny Spinach Weed (Amaranthus spinosus L.) Seeds Affected by Red Fruit Seed Liquid Smoke Doses - Anti Uni Mahanani; Miana Wenda (Institut Pertanian Bogor, 2025)
Controlling plant pests and diseases (PPD), such as the thorny amaranth weed (Amaranthus spinosus L.), is crucial to ensuring optimal plant growth and development. One option for weed control is to use organic pesticides manufactured from liquid smoke extracted from red fruit (Pandanus conoideus) seed waste. The goal of this research was to identify phenolic metabolite compounds present in liquid smoke from red fruit seed waste, analyze their effects on the germination of thorny amaranth seeds, and determine the most effective dose for minimizing weed germination. Phenolic chemicals were evaluated using GC-MS (gas chromatograph-mass spectrometer), and seed viability and vigor were assessed with liquid smoke doses of 0 mL/seed (B0), 0.1 mL/seed (B1), 0.2 mL/seed (B2), 0.3 mL/seed (B3), and 0.4 mL/seed (B4), with three replications each. The criteria assessed were phenolic chemical types, germination rate, growth potential, germination rate index, vigor index, uniformity of growth, and growth rate. The study discovered eight different types of phenolic compounds in the liquid smoke from red fruit seed waste. Liquid smoke had a significant effect on the germination and growth rates of thorny amaranth seeds, with the 0.4 mL/seed dose being the most effective at inhibiting germination, which was reduced to 0.71%. Keywords: liquid smoke, red fruit seeds, thorny spinach, viability, vigor